Design of novel lightweight high-entropy alloy of Al-Mg-Ti-Li-Ni-V series

By designing the Al-Mg-Ti-Li-Ni-V series lightweight high-entropy alloy, the limitations of existing automotive structural parts materials in terms of strength, density and safety are solved, and higher mechanical properties, lower density and higher melting point are achieved, meeting the lightweight, high strength and high safety requirements of the automotive frame.

CN119663086APending Publication Date: 2025-03-21TIANJIN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311206171.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-19
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Existing automotive structural parts materials such as aluminum alloys, magnesium alloys and high-strength steels have limitations in strength, density, melting point and safety, making it difficult to meet the lightweight, high strength and high safety requirements of automotive frames.

Method used

A new lightweight high-entropy alloy is designed, with six metal elements: Al, Mg, Ti, Li, Ni, and V. By optimizing the element ratio, the alloy is lightweight, easy to prepare and high performance.

Benefits of technology

The new lightweight high-entropy alloy has higher yield strength, tensile strength and elongation than traditional materials, while at the same time, it has lower density, higher melting point and relatively low cost, meeting the multiple needs of automotive structural parts.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a formula of a novel light high-entropy alloy of an Al-Mg-Ti-Li-Ni-V system, the novel light high-entropy alloy has good mechanical performance and low density, and the requirement of an automobile frame for materials with good plasticity and high strength ratio can be effectively met. The alloy prepared according to the method in the claim 1 is characterized in that the density of the novel alloy is 3.9-6.8 g / cm < 3 >, and compared with dual-phase steel, the density is reduced by 12-50%; the melting point is 1350-1800 DEG C and is improved by 108-177% compared with that of a magnesium alloy (the melting point is 650 DEG C); the novel alloy has good mechanical performance at normal temperature, the yield strength reaches 500-650 MPa or above, and the yield strength of the novel alloy is 10-96% higher than that of an AZ91D magnesium alloy, 7-60% higher than that of a six-series aluminum alloy and 60-110% higher than that of dual-phase steel; and the elongation rate exceeds 20-30%, is 100-200% higher than that of an AZ31B magnesium alloy and is 67-150% higher than that of a six-series aluminum alloy, and the elongation rate is equivalent to that of dual-phase steel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of high entropy alloy composition design, and particularly relates to the technical field of lightweight high entropy alloy composition design. Background Art

[0002] In modern industrial production, the automobile industry occupies a very important position. In the production process of automobiles, there are high requirements for automobile frames, wheels and other structural parts. They are required to be able to withstand large forces and produce large deformations without breaking in the event of a collision, so as to protect the safety of passengers. At the same time, in order to improve the lightweight level of the entire vehicle, the frame mass is required to be as small as possible. In order to achieve lightweight as much as possible, in addition to continuous improvements in the structural design of structural parts, replacing lighter materials is a more effective way, and using materials with better performance can give structural parts a larger structural design space. At present, most of the materials used in automobile structural parts are aluminum alloys, magnesium alloys and special high-strength steels (dual-phase steels). All three have great limitations: aluminum alloys have high yield strength, but poor elongation. The yield strength of the six-series aluminum alloy is 276MPa and the elongation is only 12%; magnesium alloys have poor ductility and low yield strength. Its yield strength is only 160MPa, and the elongation does not exceed 10%; dual-phase steel has the best mechanical properties, but has a high density, weighing 7.8g / cm 3 , which greatly affects the quality of the frame. In addition, magnesium alloys have a low melting point and are prone to spontaneous combustion. In a car accident or a fire caused by a spontaneous combustion of a car, it will cause a deflagration phenomenon, causing harm to the people in the car and threatening the personal safety of people outside the car. At the same time, the temperature of electric vehicles when they spontaneously combust is much higher than that of fuel vehicles (the spontaneous combustion temperature of electric vehicles exceeds 1000°C), and with the surge in the number of electric vehicles, magnesium alloys are becoming increasingly unsafe. Therefore, it is necessary to develop an alloy that is not less than the above three materials in strength, but has a lower density and a higher melting point, in order to address these deficiencies and shortcomings of current automobile frames.

[0003] High-entropy alloys (HEAs) are a new system of alloys proposed in 2004. They are composed of at least 5 elements and the atomic content of each element is between 5% and 35%. Due to the four major effects of high-entropy alloys: high entropy effect, lattice distortion effect, slow diffusion and "cocktail" effect, high-entropy alloys have the characteristics of high strength, wear resistance, and good high-temperature performance. However, in the early high-entropy alloys, there was a big gap between strength and plasticity, and they often could not be taken into account. In addition, most of the elements used are transition elements with high density, which makes the density of the alloy also high, and the cost is also high.

[0004] In order to meet the demand for quantization in engineering, many scholars have further proposed the concept of light weight high entropy alloy (LWHEAs). The main idea is to add a certain amount of light elements to the traditional high entropy alloys mainly composed of transition elements; or directly use light elements and a small amount of other elements to form high entropy alloys. There are three main standards for the definition of light high entropy alloys in the academic community, namely, density ρ < 3g / cm 3 High entropy alloy, ρ<4.5g / cm 3 High entropy alloy or ρ<7g / cm 3 In the present invention, the alloy density ρ<7g / cm 3 High entropy alloys are called light high entropy alloys. Light high entropy alloys have higher specific strength and better plasticity than traditional early high entropy alloys.

[0005] The present invention designs a new type of lightweight high entropy alloy, which has mechanical properties that exceed those of magnesium alloys, aluminum alloys and high-strength steels used in automobiles, has a higher melting point and is relatively low in cost. The emergence of this new type of lightweight high entropy alloy expands the scope of use of high entropy alloys and provides a possible new choice for automotive structural parts in the automotive industry. Summary of the invention

[0006] 1. A novel composition design of a lightweight high entropy alloy, characterized by comprising the following steps:

[0007] (1) Six metal elements, Al, Mg, Ti, Li, Ni, and V, are selected. Among them, Al, Mg, Ti, Li, and V are light elements (density less than 7 g / cm 3 ).

[0008] (2) The Al-Mg-Ti alloy system is used as the basic alloy system, and the atomic percentage of the three elements is guaranteed to be ≥50%, and the rest is made up by Li, Ni, and V.

[0009] (3) Based on step (2), the important elements are restricted: the atomic content of Al is 20-35%, and the atomic content of Ti is 15-20% to ensure the lightweight of the alloy.

[0010] (4) Based on step (3), the important elements are restricted: the atomic content of Mg is 3-5%, and the atomic content of Li is 3-6% to ensure the ease of preparation of the alloy.

[0011] (5) Elements not mentioned in steps (3) and (4) are adjusted according to actual property requirements, and the atomic content of the total alloy elements is completed to 100%.

[0012] 2. The alloy prepared according to the method of claim 1, characterized in that the density of the new alloy is 3.9-6.8 g / cm 3 Compared with duplex steel, the density is reduced by 12 to 50%.

[0013] 3. The alloy prepared according to the method of claim 1 is characterized in that the melting point of the new alloy is 1350-1800°C, which is 108-177% higher than that of magnesium alloy (melting point is 650°C).

[0014] 4. The alloy prepared according to the method of claim 1 is characterized in that: the new alloy has good mechanical properties at room temperature, and the yield strength reaches 500-650MPa or more, and its specific yield strength is 10-96% higher than that of AZ91D magnesium alloy; the specific yield strength is 7-60% higher than that of six-series aluminum alloy; the yield strength is 60-110% higher than that of dual-phase steel.

[0015] 5. The alloy prepared according to the method of claim 1 is characterized in that: the new alloy has good mechanical properties at room temperature, and the tensile strength is above 700-900 MPa. Its specific strength is 5-46% higher than that of AZ91D magnesium alloy; its specific strength is 12-102% higher than that of six-series aluminum alloy; and its strength is 7-37% higher than that of dual-phase steel.

[0016] 6. The alloy prepared according to the method of claim 1 is characterized in that: the new alloy has good mechanical properties at room temperature, and the elongation exceeds 20-30%. It is 100-200% higher than AZ31B magnesium alloy; it is 67-150% higher than six series aluminum alloy; the elongation of the new alloy is equivalent to that of dual-phase steel.

[0017] In short, the design idea of ​​the present invention is simple, clear, easy to repeat, and has great reference value for the invention of lightweight high entropy alloy series materials. The Al-Mg-Ti-Li-Ni-V series alloy designed by the present invention belongs to lightweight high entropy alloys, has the advantages of high specific strength and good plasticity, meets the automotive industry's demand for lightweight, high strength, and good plasticity of vehicle frames, and is expected to replace magnesium alloys, aluminum alloys, and steels, and become a good material for manufacturing vehicle frames. DETAILED DESCRIPTION

[0018] The technical solution of the present invention is further explained below in conjunction with specific implementation cases:

[0019] Implementation Plan 1

[0020] 1. A composition design of a novel lightweight high entropy alloy having an alloy composition of Al35Mg5Ti20Li5Ni5V30, characterized by comprising the following steps:

[0021] (1) Six metal elements, Al, Mg, Ti, Li, Ni, and V, are selected, among which Al, Mg, Ti, Li, and V are light elements.

[0022] (2) The Al-Mg-Ti alloy system is used as the basic alloy system, and the atomic percentage of the three elements is guaranteed to be ≥50%, and the rest is made up by Li, Ni, and V.

[0023] (3) Based on step (2), the important elements are restricted: the atomic content of Al is 35%, and the atomic content of Ti is 20% to ensure the lightweight of the alloy.

[0024] (4) Based on step (3), the important elements are restricted: the atomic content of Mg is 5%, and the atomic content of Li is 5% to ensure the manufacturability of the alloy.

[0025] (5) For the elements not mentioned in steps (3) and (4), Ni is 5%, V is 30%, and the atomic content of the total alloy elements is completed to 100%.

[0026] 2. The alloy prepared according to the method of claim 1 is characterized in that the density of the new alloy is 3.9 g / cm 3 , compared with high-strength steel for automobiles, the density is reduced by 50%.

[0027] 3. The alloy prepared according to the method of claim 1 is characterized in that the melting point of the new alloy is 1460°C, which is 125% higher than that of magnesium alloy.

[0028] 4. The alloy prepared according to the method of claim 1 is characterized in that: the new alloy has good mechanical properties at room temperature, and the yield strength reaches more than 650MPa, which is 96% higher than the yield strength of AZ91D magnesium alloy; 60% higher than the yield strength of six series aluminum alloy; and 110% higher than the yield strength of dual-phase steel.

[0029] 5. The alloy prepared by the method of claim 1 is characterized in that: the new alloy has good mechanical properties at room temperature, and the tensile strength is above 900MPa. Its specific strength is 46% higher than that of AZ91D magnesium alloy; its specific strength is 102% higher than that of six-series aluminum alloy; and its strength is 37% higher than that of dual-phase steel.

[0030] 6. The alloy prepared according to the method of claim 1 is characterized in that: the new alloy has good mechanical properties at room temperature, and the elongation exceeds 20%. Compared with AZ31B magnesium alloy, it is 100% higher; compared with six series aluminum alloy, it is 67% higher; the elongation of the new alloy is equivalent to that of dual-phase steel.

[0031] Implementation Plan 2

[0032] 1. A composition design of a novel lightweight high entropy alloy having an alloy composition of Al35Mg5Ti20Li5Ni30V5, characterized by comprising the following steps:

[0033] (1) Six metal elements, Al, Mg, Ti, Li, Ni, and V, are selected, among which Al, Mg, Ti, Li, and V are light elements.

[0034] (2) The Al-Mg-Ti alloy system is used as the basic alloy system, and the atomic percentage of the three elements is guaranteed to be ≥50%, and the rest is made up by Li, Ni, and V.

[0035] (3) Based on step (2), the important elements are restricted: the atomic content of Al is 35%, and the atomic content of Ti is 20% to ensure the lightweight of the alloy.

[0036] (4) Based on step (3), the important elements are restricted: the atomic content of Mg is 5%, and the atomic content of Li is 5% to ensure the manufacturability of the alloy.

[0037] (5) For the elements not mentioned in steps (3) and (4), Ni is 30% and V is 5%, and the atomic content of the total alloy elements is completed to 100%.

[0038] 2. The alloy prepared according to the method of claim 1 is characterized in that the density of the new alloy is 4.4 g / cm 3 , compared with high-strength steel for automobiles, the density is reduced by 44%.

[0039] 3. The alloy prepared according to the method of claim 1 is characterized in that the melting point of the new alloy is 1380°C, which is 112% higher than that of magnesium alloy.

[0040] 4. The alloy prepared according to the method of claim 1 is characterized in that: the new alloy has good mechanical properties at room temperature, and the yield strength reaches more than 600MPa, which is 53% higher than the yield strength of AZ91D magnesium alloy; 34% higher than the yield strength of six series aluminum alloy; and 94% higher than the yield strength of dual-phase steel.

[0041] 5. The alloy prepared by the method of claim 1 is characterized in that: the new alloy has good mechanical properties at room temperature, and the tensile strength is above 790MPa. Its specific strength is 15% higher than that of AZ91D magnesium alloy; its specific strength is 57% higher than that of six-series aluminum alloy; and its strength is 20% higher than that of dual-phase steel.

[0042] 6. The alloy prepared according to the method of claim 1 is characterized in that: the new alloy has good mechanical properties at room temperature, and the elongation exceeds 30%. It is 200% higher than that of AZ31B magnesium alloy; it is 150% higher than that of six series aluminum alloy; the elongation of the new alloy is equivalent to that of dual-phase steel.

[0043] Implementation Plan 3

[0044] 1. A composition design of a novel lightweight high entropy alloy having an alloy composition of Al35Mg5Ti20Li5Ni20V15, characterized by comprising the following steps:

[0045] (1) Six metal elements, Al, Mg, Ti, Li, Ni, and V, are selected, among which Al, Mg, Ti, Li, and V are light elements.

[0046] (2) The Al-Mg-Ti alloy system is used as the basic alloy system, and the atomic percentage of the three elements is guaranteed to be ≥50%, and the rest is made up by Li, Ni, and V.

[0047] (3) Based on step (2), the important elements are restricted: the atomic content of Al is 35%, and the atomic content of Ti is 20% to ensure the lightweight of the alloy.

[0048] (4) Based on step (3), the important elements are restricted: the atomic content of Mg is 5%, and the atomic content of Li is 5% to ensure the manufacturability of the alloy.

[0049] (5) For the elements not mentioned in steps (3) and (4), Ni is 20% and V is 15%, and the atomic content of the total alloy elements is completed to 100%.

[0050] 2. The alloy prepared according to the method of claim 1 is characterized in that the density of the new alloy is 4.2 g / cm 3 , compared with high-strength steel for automobiles, the density is reduced by 46%.

[0051] 3. The alloy prepared according to the method of claim 1 is characterized in that the melting point of the new alloy is 1430°C, which is 118% higher than that of magnesium alloy.

[0052] 4. The alloy prepared according to the method of claim 1 is characterized in that: the new alloy has good mechanical properties at room temperature, and the yield strength reaches above 625MPa, which is 67% higher than the yield strength of AZ91D magnesium alloy; 47% higher than the yield strength of six series aluminum alloy; and the yield strength is 102% higher than that of dual-phase steel.

[0053] 5. The alloy prepared according to the method of claim 1 is characterized in that: the new alloy has good mechanical properties at room temperature, and the tensile strength is above 840MPa. Its specific strength is 30% higher than that of AZ91D magnesium alloy; its specific strength is 75% higher than that of six-series aluminum alloy; and its strength is 28% higher than that of dual-phase steel.

[0054] 6. The alloy prepared according to the method of claim 1 is characterized in that: the new alloy has good mechanical properties at room temperature, and the elongation exceeds 26%. Compared with AZ31B magnesium alloy, it is 160% higher; compared with six series aluminum alloy, it is 117% higher; the elongation of the new alloy is equivalent to that of dual-phase steel.

[0055] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.

Claims

1. A novel lightweight high entropy alloy composition design, characterized by The following steps are involved: (1) Six metal elements, Al, Mg, Ti, Li, Ni, and V, are selected, among which Al, Mg, Ti, Li, and V are light elements. (2) The Al-Mg-Ti alloy system is used as the basic alloy system, and the atomic percentage of the three elements is guaranteed to be ≥50%, and the rest is made up by Li, Ni, and V. (3) Based on step (2), the important elements are restricted: the atomic content of Al is 20-35%, and the atomic content of Ti is 15-20% to ensure the lightweight of the alloy. (4) Based on step (3), the important elements are restricted: the atomic content of Mg is 3-5%, and the atomic content of Li is 3-6% to ensure the manufacturability of the alloy. (5) Elements not mentioned in steps (3) and (4) are adjusted according to actual property requirements, and the atomic content of the total alloy elements is completed to 100%.

2. The alloy prepared according to the method of claim 1, characterized in that: The density of the new alloy is 3.9~6.8g / cm 3 Compared with duplex steel, the density is reduced by 12 to 50%.

3. The alloy prepared according to the method of claim 1, characterized in that: The melting point of the new alloy is between 1350 and 1800°C, which is 108 to 177% higher than that of magnesium alloy.

4. The alloy prepared according to the method of claim 1, characterized in that: The new alloy has good mechanical properties at room temperature, and its yield strength reaches 500-650MPa or above. Its yield strength is 10-96% higher than that of AZ91D magnesium alloy; 7-60% higher than that of six-series aluminum alloy; and its yield strength is 60-110% higher than that of dual-phase steel.

5. The alloy prepared according to the method of claim 1, characterized in that: The new alloy has good mechanical properties at room temperature, with a tensile strength of 700-900 MPa or more. Its specific strength is 5-46% higher than that of AZ91D magnesium alloy, 12-102% higher than that of six-series aluminum alloy, and 7-37% higher than that of dual-phase steel.

6. The alloy prepared according to the method of claim 1, characterized in that: The new alloy has good mechanical properties at room temperature, with an elongation of more than 20-30%, which is 100-200% higher than AZ31B magnesium alloy and 67-150% higher than six-series aluminum alloy. The elongation of the new alloy is equivalent to that of dual-phase steel.